Analytical and experimental study of air permeability of external walls of buildings on railway transport - Adilhodjaev A.I.; Shaumarov S.S.; Kandakharov S.I. (Научно-технический вестник Брянского государственного университета)
The issue of thermal renewal of railway transport infrastructure facilities was considered. The physical influence of the external environment on the formation of the indoor indoor microclimate was studied.